Association between EGF, TGF-β1, TNF-α gene polymorphisms and cancer of the pancreatic head - Wu, Guo-Yang; Lu, Qingjun; Hasenberg, Till; Niedergethmann, Marco; Post, Stefan; Sturm, Jörg; Keese, Michael (Anticancer research, 2010)
Background: To date, EGF 61*A/G, TGF-β1 -509*T/C and TNF-α -308*A/G gene polymorphisms have been not been analysed in pancreatic carcinoma. This study investigated the frequency of these gene polymorphisms among patients with cancer of the pancreatic head. Patients and Methods: A total of 73 pancreatic head cancer patients and 117 cancer-free healthy people were recruited at the Surgical Department of the University Hospital Mannheim. Genomic DNA was isolated from peripheral blood and gene polymorphisms were analysed by PCR-RFLP. Results: The distribution of EGF 61*G/G homozygotes among pancreatic head cancer patients was more frequent than that in the control group (24.7% vs 11.1%, odds ratio (OR)=2.618, 95% confidence interval (CI)=1.195-5.738). In addition, the frequency of the G allele in the pancreatic head cancer patient group was also higher than that in the control group (45.9% vs. 33.3%, OR=1.696, 95% CI=1.110-2.592). No difference was found for the TGF-β1 -509 and TNF-α -308 genotypes among pancreatic head cancer patients and healthy controls. Conclusion: The frequencies of the EGF 61*G/G genotype and G allele are significantly increased among patients with pancreatic head cancer. TGF-β1-509*T/C and TNF-α -308*A/G gene polymorphisms are not related to this cancer entity.
Gesehen am 30.04.2024